Pendidikan & Pengembangan Anak Pesisir Pantai Melalui Kegiatan Bermain dan Belajar Bersama untuk Meningkatkan Kreativitas dan Pengetahuan di Komunitas Lokal - Nurul Hidayat; Cici Agustina Bp; Marcelina Bidang; Andi Syazwanie; Lilis Lilis; Aykel Farel (STIKes Ibnu Sina Ajibarang, 2024)
Strengthening literacy for children is very important, literacy is related to mastery of reading and writing. Lack of attention and instilling literacy from an early age causes a region to experience a low literacy level. The aim of this service activity is to increase understanding and literacy knowledge of coastal children, assist and strengthen children's literacy through playing activities, learning to write and read. This activity is carried out in several stages such as the preparation stage, activity stage, and final evaluation stage. This activity was attended by coastal children. The results that occurred at the activity stage were a lack of knowledge and assistance from families, especially parents, towards children about the importance of literacy for the child's future, resulting in a lack of interest in reading in children. This activity can provide benefits to the community, especially the coastal children of Amal Beach Village, East Tarakan, Tarakan.